A prospective study: role of prophylactic antibiotics versus no antibiotics in elective laparoscopic cholecystectomy - Verma, Renu; Mittal, Sushil Kumar; Singla, Navdeep Kumar (International Surgery Journal, 2020)
Background: Elective gallbladder surgery is the most common abdominal surgical procedure. Antibiotic prophylaxis is a common conduct in open cholecystectomy, but there is ambiguity about the use of prophylactic antibiotics in laparoscopic cholecystectomy. Some surgeons suggest that the elimination of prophylactic antibiotics in patients undergoing elective laparoscopic cholecystectomy increase the incidence of postoperative infective complications but not to a statistically significant degree. The aim of this study was to evaluate the role of prophylactic antibiotics in laparoscopic cholecystectomy. Methods: A total of 100 patients were included and they were randomized in 2 groups of 50 each. Group A was given prophylactic intravenously (IV) antibiotic within 1 hour before surgery and group B was not given any antibiotics. Results were compared and data analyzed statistically using chi-square and t test. Complications in both the groups were compared. Results: Rate of surgical site infections were 6% (n=3) and 4% (n=2) in group A and B respectively; and the difference between them was not found statistically significant. All infections which occurred in present study were superficial surgical site infection. There was no evidence of deep-seated infections and none of the patients developed distant infection. There was no derangement in any of the biochemical parameter in this study. Conclusions: We were not able to demonstrate any significant benefit from addition of prophylactic antibiotics in elective laparoscopic cholecystectomy.